Cnidarians and the evolutionary origin of the nervous system - Watanabe, Hiroshi; Fujisawa, Toshitaka; Holstein, Thomas W. (Development, growth & differentiation, 2009)
Cnidarians are widely regarded as one of the first organisms in animal evolution possessing a nervous system. Conventional histological and electrophysiological studies have revealed a considerable degree of complexity of the cnidarian nervous system. Thanks to expressed sequence tags and genome projects and the availability of functional assay systems in cnidarians, this simple nervous system is now genetically accessible and becomes particularly valuable for understanding the origin and evolution of the genetic control mechanisms underlying its development. In the present review, the anatomical and physiological features of the cnidarian nervous system and the interesting parallels in neurodevelopmental mechanisms between Cnidaria and Bilateria are discussed.